Transferrin receptor 2 controls bone mass and pathological bone formation via BMP and Wnt signalling - Rauner, Martina; Altamura, Sandro; Colucci, Silvia; Muckenthaler, Martina (Nature metabolism, 2019)
Transferrin receptor 2 (Trf2) is known to regulate iron homeostasis through its action in the liver. Here the authors report a previously unrecognised role of Trf2 in regulating bone homeostasis mediated by modulation of BMP signalling specifically on osteoblasts.
Gesehen am 07.04.2020